FTIR, UV–Vis–NIR spectroscopy, and gamma rays shielding competence of novel ZnO-doped vanadium borophosphate glasses - Rammah, Y. S.; El-Agawany, F. I.; Mahmoud, K. A.; El-Mallawany, R.; Ilik, Erkan; Kilic, Gokhan (Journal of materials science. Materials in electronics, 2020)
Structural, optical, and gamma radiation safety properties of 46V 2 O 5 ·46P 2 O 5 ·(8– x )B 2 O 3 · x ZnO ( x = 0,2,4,6, and 8 mol%) abbreviated as VPB/Zn glasses were investigated. The structure of the synthesized glasses has been examined via FTIR spectra within the range of 400–1500 cm −1 at room temperature. UV–Vis–NIR measurements of the proposed glasses were performed within the range of 200–3300 nm. The optical characteristics such as optical energy bandgap ( E Optical ), refractive index ( n Linear ), and Urbach’s energy ( E U ) have been determined. In addition, the mass attenuation coefficients (MAC) for VPB/Zn glasses were performed utilizing MCNP-5 simulation code and XCOM program for various gamma ray energy varied in range 0.015–15 MeV. Based on MAC values, the equivalent atomic number ( Z eq ) and buildup factors (EABF and EBF) were evaluated. Results reveal that the direct E Optical Tauc ′ s of the VPB/Zn glasses ranged from 0.688 to 0.710 eV, while from 0.560 to 0.647 eV for the indirect transition. The admission of the ZnO improves the MAC of the VPB/Zn glasses. Thus, one can conclude that the proposed glasses can be applied for optical devices as semiconductor glasses and considered as good materials for γ-rays shielding.